INVIGORASI BENIH PADI (Oryza sativa L.) KADALUARSA DENGAN AIR KELAPA - Robby Sanjaya; Ardaniah Ardaniah; Primadiyanti Arsela (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study aimed to evaluate the response of expired rice seeds to natural plant growth regulators (PGR) and different soaking durations in coconut water. The experiment used expired rice seeds and fresh young coconut water arranged in a factorial Completely Randomized Design (CRD) consisting of six treatments with three replications. Data were analyzed using factorial analysis of variance followed by the Honestly Significant Difference (HSD) test. Results showed that coconut water concentrations of 10–30% combined with soaking durations of 2–6 hours did not significantly affect germination percentage, vigor index, germination rate, germination speed (P>0.05). However, soaking seeds for six hours indicated a tendency toward improved seed performance. Longer soaking periods enhanced water absorption, improved tissue hydration, and stimulated early metabolic activities necessary for germination. These findings suggest that extended soaking duration help restore physiological activity in expired seeds, although the treatments tested did not produce statistically significant differences.